2017
DOI: 10.1638/2016-0003.1
|View full text |Cite
|
Sign up to set email alerts
|

STRESS INFLUENCE ON PLASMA PROTEIN ELECTROPHORESIS IN THE RED-BREASTED GOOSE (BRANTA RUFICOLLIS) AND HAWAIIAN GOOSE (BRANTA SANDVICENSIS)

Abstract: The objective of this study was to evaluate the effects of stress (as measured by total heterophil + eosinophil counts [THECs] and plasma corticosterone [PC] levels) on plasma protein electrophoresis (PPE) in two Anseriform species. Ten red-breasted geese ( Branta ruficollis ) and eight Hawaiian geese (Branta sandvicensis) were received into quarantine at Beauval Zoo and housed together with other Anseriformes. Two days later, all were examined as part of routine quarantine procedures, and blood was collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…86,108,112 In the red-breasted and Hawaiian goose species, the prealbumin migrating fraction level was observed to decrease with increased corticosterone levels, associated with increased stress relative to transport and quarantine. 113 EPH has been used as an adjunct tool in the diagnosis of infectious diseases, including chlamydiosis, aspergillosis, sarcocystosis, bornavirus infection, and mycobacteriosis. [52][53][54][55][56][57][58][59][60]64 In a study of African penguins with presumed or confirmed aspergillosis, a significant increase in alpha 2 globulins was associated with a specificity of 92% and a negative predictive value of 81%.…”
Section: Avian S Pecie Smentioning
confidence: 99%
“…86,108,112 In the red-breasted and Hawaiian goose species, the prealbumin migrating fraction level was observed to decrease with increased corticosterone levels, associated with increased stress relative to transport and quarantine. 113 EPH has been used as an adjunct tool in the diagnosis of infectious diseases, including chlamydiosis, aspergillosis, sarcocystosis, bornavirus infection, and mycobacteriosis. [52][53][54][55][56][57][58][59][60]64 In a study of African penguins with presumed or confirmed aspergillosis, a significant increase in alpha 2 globulins was associated with a specificity of 92% and a negative predictive value of 81%.…”
Section: Avian S Pecie Smentioning
confidence: 99%
“…It is known that the erythrocytes (red blood cells) or birds are nucleated and larger than cells of mammals. The heterophiles have similar function to the neutrophils in mammals and are the main phagocytic cells involved in the inflammatory response (Capitelli & Crosta, 2013), besides being considered stress markers in some studies with birds, and there is also a correlation value between lymphocytes and heterophile known as an indicator of chronic stress in birds (Leclerc et al, 2017;Ludwig et al, 2017). Whereas the thrombocytes have functions related to hemostasis and the thromboplastin production, but also perform phagocytic function.…”
Section: Introductionmentioning
confidence: 99%